Implementation of Music Arts Learning in Culture Arts Lessons at Elementary School in Pontianak Municipality - Ghozali, Imam; Sumaryanto F., Totok; Utomo, Udi (Universitas Negeri Semarang, 2018)
Art is multilingual, multidimensional, and multicultural. The special characters that art possesses are aesthetic, expressive, and creative all of which are integral parts of each other. The teaching of arts in elementary school is left to class teachers who are generally very limited in terms of their cognitive, affective, or psychomotoric aspects. It allows the gap in arts education in elementary school so it is necessary to research how the implementation of music arts learning in elementary school is.This research uses qualitative method with descriptive analytical procedures. The main data sources of this study were elementary school teachers while the supporting data sources were students and principal. The data collection techniques include observations, interviews, and documentary studies. The data were tested for their validity with the triangulation technique. The data analysis techniques included interactive analysis models. The results of study which was located in apublic elementary school and two private elementary schools showthe tendency of certain grouping pattern in the learning processes. The background, interest, and arts potential are the factors that influence the grouping. The integrative thematic approach in arts learning can cause the teacher to become less focused, the frequency of meetings is not constant, and material staging is rather difficult to do. In general, the learning processes were generally textbook oriented.